The effect of Beetle leaves (Piper Betle Linn) for dental caries formation - Kurniawan, Adi; Andang, Milly Armilya; Hayati, Ayu Trisna (Padjadjaran Journal of Dentistry, 2007)
Dental caries is still the main problem in dental and oral health. Caries is caused by several factors working simultaneously. The main principle of management caries is by prioritizing preventive action and avoiding invasive action. Beetle leaves are medicamentous plant which are widely cultivated and very beneficial for Indonesian people. Its active content enable beetle leaves to be used as antimicrobial, antiseptic, antifungal, antioxidant, and disinfectant. The government of Indonesia and WHO greatly support the utilization of natural resources as medical cure. Currently we can find a lot of toothpaste and mouthwash products which use beetle leaves as additional ingredient. Various researches have proved that the use of beetle leaves extract as mouthwash, toothpaste and chewing beetle leaves may decrease plaque score. Chavicol and chavibetol content enable beetle leaves to function as very good antimicrobial. Beetle leaves also contain charvacrol, eugenol, methyl eugenol, cadinene, and seskuiterpene, which can function as antiseptic. Beetle leaves may effect salivary function and secretion and also impede the forming of dental caries.